Pemahaman Generasi Milenial Madrasah Ibtidaiyah Terhadap Ajaran Islam dalam Era Revolusi Industri 4.0 di Indonesia: Studi Kasus pada Tingkat Dasar. - Qomarudin, Muslih (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2024)
This research explores the comprehension of Islamic teachings among the millennial generation at Madrasah Ibtidaiyah (MI) in the context of Indonesia's Industry 4.0 Revolution, focusing on elementary education. The study addresses three primary aspects: the understanding of Islamic teachings by the millennial generation at MI, the factors influencing this understanding, and strategies to improve comprehension within the Industry 4.0 framework. Utilizing a qualitative approach, the case study at MI Roudhotu Tolibin Bumi Agung Way Kanan reveals several key findings. These findings include imagination and creativity related to religious values, basic moral understanding, familiarity with worship rituals, awareness of the stories of prophets and messengers, engagement in religious activities, curiosity, role-playing, and symbolism. Despite this, essential concepts are not fully grasped. Factors affecting the understanding of Islamic teachings among MI millennial students involve a complex interplay of education and teaching, family influence, the madrasah environment, social interactions, media and technology, and personal factors. Strategies to enhance comprehension include interactive teaching methods, the use of media and technology, practical activities, contextual learning, religious activities, and parental involvement.